Housing and children's development and wellbeing: a scoping study - Dockery, A.M.; Strazdins, L; Li, J; Ong, R; Kendall, G; Mahendran, A (AHURI, 2010)
This scoping study reviewed existing literature on the connections between housing and childhood development and wellbeing it investigates the value and feasibility of conducting empirical research in the Australian context.
AHURI Final Report no. 149
Final Reports
Keywords: Housing; Health -- Wellbeing; Child Development; Health; Childhood and child development; Health and wellbeing; Child Development; Housing; Health; Wellbeing; Health and wellbeing; Childhood and child development